Hollywood Muslims in Iraq - Petersen, Kristian (Journal of religion and popular culture, 2017)
This essay explores how Muslims are represented in the two most successful Iraq War films, American Sniper (2014, US) and The Hurt Locker (2008, US), and offers a comparative analysis of the cultural assertions being deployed in their representation. To do this, I provide a close reading of the films' depictions within visual, discursive, and sonic fields of production and show how their representations of Muslims signify specific meanings to the audience, which render Muslims distrustful, threatening, and uncivilized, thereby legitimizing specific oppressive treatment and policies toward them.